Calculating tidal prediction in the Gulf of Tonkin - Quynh, Do Ngoc; Viet Lien, Nguyen Thi (Vietnam Journal of Mechanics, 1995)
In the paper the using numerical hydro dynamical model for the tidal prediction in the Gulf of Tonkin is presented. The results of prediction are compared with the Tidal Table at some coastal station. The comparison proves that the prediction model suits practice.